The Pre-Lumbar puncture Intracranial Hypertension Scale (PLIHS): A practical scale to identify subjects with normal cerebrospinal fluid pressure in the management of idiopathic intracranial hypertension - Raggi, Alberto; Bianchi Marzoli, Stefania; Ciasca, Paola; Cammarata, Gabriella; Melzi, Lisa; Chiapparini, Luisa; Erbetta, Alessandra; Ciceri, Elisa; Faragò, Giuseppe; Gioppo, Andrea; Usai, Susanna; D'Amico, Domenico (Journal of the neurological sciences, 2021)
Idiopathic Intracranial Hypertension (IIH) diagnosis requires lumbar puncture to measure cerebrospinal fluid (CSF) pressure. The Pre-Lumbar puncture Intracranial Hypertension Scale (PLIHS) is aimed to detect cases that will show raised or normal CSF opening pressure. Retrospective analysis of records of patients who underwent lumbar puncture for suspect IIH. The target was CSF opening pressure ≥ 250 mmH2O, whereas a set of known neurological, neuro-ophthalmological and neuro-radiological parameters, plus obesity, were used as predictors in a logistic regression model. The PLIHS was based on significant predictors and a cut-off was validated using chi-squared test around CSF opening pressure ≥ 250 and < 200 mmH2O. Records of 162 patients were included: CSF opening pressure was <200 mmH2O in 40 and ≥ 250 mmH2O in 95 patients; 85 fulfilled IIH diagnosis. PLIHS is based on Frisén grade 2 or higher papilledema, tinnitus, empty sella, perioptic subarachnoid space distension, and obesity. Score range is 0–7: correlation with CSF opening pressure is 0.508 (p < .001), and PLIHS score is different between subjects not diagnosed with IIH, and those diagnosed with IIH both with and without papilledema (p < .001). PLIHS score ≤ 2 identifies cerebrospinal fluid pressure < 200 mmH2O; PLIHS score ≥ 3 identifies CSF opening pressure ≥ 250 mmH2O, IIH diagnosis, visual acuity ≤0.7, and optic nerve atrophy. The PLIHS, can be used to identify patients who will particularly need LP, thus helping with the organization of the diagnostic work-up by optimising healthcare resources and potentially limit the likelihood to incur in LP-related adverse events. •LP is necessary to measure CSF pressure and appoint IIH diagnosis.•The PLIHS aimed to identify patients with raised or normal CSF pressure.•PLIHS score ≤ 2 identifies CSF opening pressure < 200 mmH2O.•PLIHS score ≥ 3 identifies CSF opening pressure ≥ 250 mmH2O and IIH diagnosis.•The PLIHS can be used to prioritize patients with LP.